2015
DOI: 10.1371/journal.pone.0145316
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput qPCR Expression Profiling of Circulating MicroRNAs Reveals Minimal Sex- and Sample Timing-Related Variation in Plasma of Healthy Volunteers

Abstract: MicroRNAs are a class of small non-coding RNA that regulate gene expression at a post-transcriptional level. MicroRNAs have been identified in various body fluids under normal conditions and their stability as well as their dysregulation in disease opens up a new field for biomarker study. However, diurnal and day-to-day variation in plasma microRNA levels, and differential regulation between males and females, may affect biomarker stability. A QuantStudio 12K Flex Real-Time PCR System was used to profile plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 49 publications
5
34
1
Order By: Relevance
“… and can be detected in all peripheral fluids including saliva, serum, plasma, cerebral spinal fluid (CSF), and urine . Compared to protein biomarkers, miRNAs offer several advantages: (1) they are stable in bodily fluids; (2) they do not get modified; (3) many have restricted expression in the tissues they regulate; (4) preliminary studies indicate little variation between sexes, age, or time of sampling; and (5) they are easily and accurately quantified by routine and fast laboratory methods (such as reverse transcription polymerase chain reaction) that are available in most clinical laboratory settings. With respect to PD, the expression levels of many miRNAs are altered in the different regions of PD brain (reviewed in refs.…”
mentioning
confidence: 99%
“… and can be detected in all peripheral fluids including saliva, serum, plasma, cerebral spinal fluid (CSF), and urine . Compared to protein biomarkers, miRNAs offer several advantages: (1) they are stable in bodily fluids; (2) they do not get modified; (3) many have restricted expression in the tissues they regulate; (4) preliminary studies indicate little variation between sexes, age, or time of sampling; and (5) they are easily and accurately quantified by routine and fast laboratory methods (such as reverse transcription polymerase chain reaction) that are available in most clinical laboratory settings. With respect to PD, the expression levels of many miRNAs are altered in the different regions of PD brain (reviewed in refs.…”
mentioning
confidence: 99%
“…One small study (n = 18) reported 40 miRNAs that were differentially expressed by sex in the human prefrontal cortex [20]. A few studies have examined sex-related differences in profiles of circulating plasma miRNAs in adults but were limited either by small sample size or low number of miRNAs assessed [36][37][38][39]. For example, one study found no differences by sex in miRNA expression of 108 miRNAs characterized in 20 adults [39].…”
mentioning
confidence: 99%
“…A few studies have examined sex-related differences in profiles of circulating plasma miRNAs in adults but were limited either by small sample size or low number of miRNAs assessed [36][37][38][39]. For example, one study found no differences by sex in miRNA expression of 108 miRNAs characterized in 20 adults [39]. In another human study, (n = 18) four miRNAs (out of 534 miRNAs) were significantly upregulated in women [38], while yet another study reported seven out of 179 candidate miRNAs to be differentially expressed by sex [36].…”
mentioning
confidence: 99%
“…Absorbance of hemoglobin in some samples indicated values >0.25 (Fig. C), which was set as an upper limit …”
Section: Plasma Quality Controlmentioning
confidence: 99%
“…An alternative method is to measure hemoglobin at 414 nm and use a cutoff absorbance value of 0.20-0.25. [18][19][20] Although not a typical problem in rat samples, it should be noted that lipemia in plasma interferes with hemoglobin absorbance, which may cause an increase in absorbance values, even in the absence of any hemoglobinrelated peak. 21 By also measuring the plasma absorbance at 385 nm (as a lipemia indicator) it is possible to identify hemolyzed samples, independent of lipemia.…”
Section: Plasma Quality Controlmentioning
confidence: 99%